Evaluation of psychometric properties and factorial structure of the pre-school child behaviour checklist at the Kenyan Coast - Kariuki, S; Abubakar, A; Murray, E; Stein, A; Newton, C (BioMed Central, 2016)

(untitled)
Background: Behavioural/emotional problems may be common in preschool children living in resource-poor settings, but assessment of these problems in preschool children from poor areas is challenging owing to lack of appropriate behavioural screening tools. The child behaviour checklist (CBCL) is widely known for its reliability in identifying behavioural/emotional problems in preschool children, but it has not been validated for use in sub-Saharan Africa. Methods: With permission from developers of CBCL, we translated this tool into Ki-Swahili and adapted the items to make them culturally appropriate and contextually relevant and examined the psychometric properties of the CBCL, particularly reliability, validity and factorial structure in a Kenyan community preschool sample of 301 children. It was also re-administered after 2 weeks to 38 randomly selected respondents, for the purpose of evaluating retest reliability. To evaluate inter-informant reliability, the CBCL was administered to 46 respondents (17 alternative caretakers and 29 fathers) alongside the child’s mother. Generalised linear model was used to measure associations with behavioural/emotional scores. We used structural equation modelling to perform a confirmatory factor analysis to examine the seven-syndrome CBCL structure. Results: During the first phase we found that most of the items could be adequately translated and easily understood by the participants. The inter-informant agreement for CBCL scores was excellent between the mothers and other caretakers [Pearson’s correlation coefficient (r) = 0.89, p < 0.001] and fathers (r = 0.81; p < 0.001). The test–retest reliability was acceptable (r = 0.76; p < 0.001). The scale internal consistency coefficients were excellent for total problems [Cronbach’s alpha (α) = 0.95] and between good and excellent for most CBCL sub-scales (α = 0.65–0.86). Behavioural/emotional scores were associated with pregnancy complications [adjusted beta coefficient (β) = 0.44 (95 % CI, 0.07–0.81)] and adverse perinatal events [β = 0.61 (95 % CI, 0.09–1.13)] suggesting discriminant validity of the CBCL. Most fit indices for the seven-syndrome CBCL structure were within acceptable range, being <0.09 for root mean squared error of approximation and >0.90 for Tucker–Lewis Index and Comparative Fit Index. Conclusion: The CBCL has good psychometric properties and the seven-syndrome structure fits well with the Kenyan preschool children suggesting it can be used to assess behavioural/emotional problems in this rural area.